The reciprocal relationship between job insecurity and depressive symptoms: A latent transition analysis. (28th November 2017) - Vander Elst, Tinne; Notelaers, Guy; Skogstad, Anders
Summary: Previous studies on the relationship between job insecurity and depressive symptoms have mainly focused on the stressor‐to‐strain effect from job insecurity to depressive symptoms, on rather secure and healthy employees, and on rank‐order relationships. This is not entirely in line with stress theories suggesting intraindividual and reciprocal relationships between high levels of stressors and strain. In reply, this study investigated whether high levels of job insecurity were related to subsequent high levels of depressive symptoms, and vice versa. Cross‐lagged dual process latent Markov model analysis with 3‐wave data (time lags of 2 and 3 years) from a representative sample of the Norwegian working force ( N  = 2, 539) revealed 5 latent states of job insecurity and 6 latent states of depressive symptoms. As hypothesized, a reciprocal relationship between the "high job insecurity" state and the "depressed" state was found: Previously highly job‐insecure employees were more likely to be depressed at the next measurement point ( OR  = 42.54), and employees labeled as depressed were more likely to experience high job insecurity later on ( OR  = 69.92). This study contributes to stress theory by demonstrating that stressors and strain may relate differently depending on the level of stressor and strain experienced.